Investigation of Change in Team Dynamics Over Time: From F2F to Facebook Setting - Varol, Filiz (Kamla-Raj Enterprises, 2015)
This study investigates how teams' Shared Mental Models (SMMs) change in a computer supported collaborative learning environment and how their SMM scores change in such environments after being exposed to team-based learning in a face-to-face setting:A total of 57 pre-service teachers enrolled in a blended course participated, forming groups of three to five. The teams completed three in-class activities followed,by three assignments provided via an asynchronous learning environment. A questionnaire was administered after each assignment. Data was analyzed using a repeated measures ANOVA. At first, the participants appreciated the group work, but their appreciation levels decreased after the first assignment. As they were able to solve issues, they placed more value on teams. Ultimately, SMM scores were higher in the online learning environment compared with the face-to-face setting. Also, with time the learners were better able to exchange information, solve problems, make decisions, openly discuss issue's, and complete assignments effectively.
Keywords: Team-based Learning; Team Shared Mental Model; Computer Supported Collaborative Learning Environment; Face-to-face